Urbanization’s Effects on Problem Solving Abilities: A Meta-Analysis - Vincze, Ernő; Kovács, Bálint (Frontiers in Ecology and Evolution, 2022)
Cognitive abilities are often assumed to be advantageous in urban habitats, but relatively few studies tested this assumption. In a meta-analysis, we tested whether urban animals have better problem-solving abilities compared to their less urbanized conspecifics. After screening 210 papers we collected by keyword search and forward search, we found 12 studies that compared the ability to solve food-extraction or obstacle-removal problems between urban and non-urban populations of the same animal species. These studies were published between 2009 and 2021, and were performed mostly on birds, whereas a quarter of them used mammals as study species. We found a statistically non-significant trend that urban animals are more successful and faster problem-solvers compared to their less urbanized conspecifics. However, both solving success and solving latency effect sizes were highly heterogeneous, therefore hard to generalize. Though the sample was too low to test the factors explaining this high heterogeneity, we suggest that it may be explained by variation in task types, study species, definitions of urbanization, whether the study was performed on captive or free-living animals, geographical location, or publication bias in both directions. Altogether, more studies are needed to either confirm or disprove this trend.